2014
DOI: 10.1021/jm5013159
|View full text |Cite
|
Sign up to set email alerts
|

Combining X-ray Crystallography and Molecular Modeling toward the Optimization of Pyrazolo[3,4-d]pyrimidines as Potent c-Src Inhibitors Active in Vivo against Neuroblastoma

Abstract: c-Src is a tyrosine kinase belonging to the Src-family kinases. It is overexpressed and/or hyperactivated in a variety of cancer cells, thus its inhibition has been predicted to have therapeutic effects in solid tumors. Recently, the pyrazolo[3,4-d]pyrimidine 3 was reported as a dual c-Src/Abl inhibitor. Herein we describe a multidisciplinary drug discovery approach for the optimization of the lead 3 against c-Src. Starting from the X-ray crystal structure of c-Src in complex with 3, Monte Carlo free energy pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 57 publications
3
73
0
Order By: Relevance
“…1A) thanks to its favorable and previously characterized set of ADME and activity properties (13). The compound exhibited the ability to inhibit c-SRC tyrosine kinase in cell-free assays at micromolar concentration.…”
Section: Introductionmentioning
confidence: 99%
“…1A) thanks to its favorable and previously characterized set of ADME and activity properties (13). The compound exhibited the ability to inhibit c-SRC tyrosine kinase in cell-free assays at micromolar concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazolo [3,4-d] pyrimidine derivatives display a broad spectrum of biological properties, such as antiviral (Bektemirov et al, 1981), antibacterial (Rostamizadeh et al, 2013) and antitumor (Tintori et al, 2015). The present work is a continuation of our studies of pyrazolo [3,4-d]pyrimidine derivatives (El Hafi et al, 2017).…”
Section: Structure Descriptionmentioning
confidence: 70%
“…Schenone et al have reported a wide library of potent KIs endowed with a pyrazolo[3,4-d] pyrimidine scaffold [17,18]. Many of these compounds are active on different cancer cell lines, and some also showed activity in in vivo mouse models [19,20]. Among the members of this library, compound SI214 ( Figure 1a) is a potent Src inhibitor (K i = 90 nM) and possesses a considerable antiproliferative effect on the SH-SY5Y Neuroblastoma cell line (IC 50 = 80 nM).…”
Section: Introductionmentioning
confidence: 99%